Development of 10.9 Grade 32CrB4 Quenched and Tempered Round Steel for Fasteners - Peng Feng, Li Xu, Li Bopeng, Zhang Yue, Wang Zhanzhong, Guo Shibei (Teshugang)
There is an urgent need to develop low-cost， high-strength， and toughness grades of steel for domestic wind power fasteners in order to enhance the competitiveness of the industrial chain and fully participate in market competition. Through the control of smelting process to assure residual w ［P］≤0.015% and w［S］≤ 0.010% and the total oxygen content w［T.O］ stably controlled to be less than 10 × 10-6 during low oxygen operation practice. Two stage low-temperature rolling is adopted and the single pass reduction rate is controlled between 8% to 12%. A 10.9-grade 32CrB4 bolt steel with good impact toughness at -40 ℃ low-temperature for 38.8 mm specification has been successfully developed. The results of mechanical property inspection and metallographic observation indicate that the developed steel has good tensile properties and excellent low-temperature impact properties. The optimal heat treatment process has been studied， which is 820 ℃ soaking water quenching and 510 ℃ soaking tempering. The room temperature tensile strength can reach 1 075 MPa， and the average low-temperature impact value of -40 ℃ KV2 can be 53 J. The microstructure is mainly tempered martensite， with excellent and comprehensive mechanical properties and good uniformity.